2016
DOI: 10.24953/turkjped.2016.01.008
|View full text |Cite
|
Sign up to set email alerts
|

The comparison of general movements assessment and neurological examination during early infancy

Abstract: This prospective single-blinded study was performed to evaluate general movements (GMs) in group of high-risk, low-birth-weight and preterm infants and to compare results with neurologic examination. All infants' neurologic examinations, Gross Motor Function Measurement (GMFM) and Bayley-III Scale were performed at the corrected age of 12 months. A total of 22 infants were included. Eight infants (group-1) (mean: 31.6±3.29 weeks, range: 25-36 weeks) had normal GMs in all recordings and were ultimately evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…29 In Turkey, a prospective single-blinded study was done with 22 preterm infants that supported high consistency between fidgety movements and neurologic outcomes. 30 Fuentefria et al 3 reviewed 23 studies including preterm infants and reported that the AIMS assessment in infants varied from 5 months until 18 months. These studies showed significant differences in motor developmental delay between preterm and full-term infants, with a description of lower gross scores in the AIMS results for preterm infants.…”
Section: Discussionmentioning
confidence: 99%
“…29 In Turkey, a prospective single-blinded study was done with 22 preterm infants that supported high consistency between fidgety movements and neurologic outcomes. 30 Fuentefria et al 3 reviewed 23 studies including preterm infants and reported that the AIMS assessment in infants varied from 5 months until 18 months. These studies showed significant differences in motor developmental delay between preterm and full-term infants, with a description of lower gross scores in the AIMS results for preterm infants.…”
Section: Discussionmentioning
confidence: 99%